Multivariate analysis in cytoplasmic male sterile lines of rice (Oryza sativa L.) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 25-28